Analysis Of Functional Build (FB) In Aluminium Extrusion Process Innovation By Using Arena Software - Mohd Yusof, Taib (2010)

(untitled)
Product innovation plays important role in ensuring the continuity and growth of a business. Shorter production time and less defect quantity will be the main subject in order to increase profit. Thus, development of innovation model is a need to make sure that the business is successful from time to time. Innovation model that will be discussed in this paper is related to Functional Build (FB) in aluminium extrusion process. FB is a concept that allows a certain extent of variation to process specifications whilst maintaining the overall output specification which the customer would see. A new model of innovation process was developed based on numerous literatures with the focus of improving the production ramp-up stage of the process. This paper introduced the idea of permitting the extruded sections which associated with minor surface imperfections to progress to the next operations since they were proven to be removed during the anodising operation. Both the previous and new aluminium extrusion processes were simulated by using Arena simulation software version 5.0 to analyse the expected improvement of rejection level and production time. Simulation results showed that the rejected level of extruded sections was reduced by 57.14% and total processing time was reduced by 8.04%. Hence, it is proven that the application of FB approach in innovation process of aluminium extrusion products development can help businesses to reduce the product development lead time and facilitate them to become more innovative.